The Process of Knowledge Acquiring in Nursing Education: Grounded Theory - Zahra Marzieh Hassanian; MohammadReza Ahanchian; Hossein Karimi-Moonaghi (Research and Development in Medical Education, 2018)
Background: Knowledge acquisition, as a part of knowledge management, plays a valuable role in nursing education. Hence, the education system seeks strategies that allow nursing faculty members and students to acquire knowledge and build experiences. The present study explores the process of acquiring knowledge in nursing education. Methods: In this study, which was carried out in Mashhad School of Nursing and Midwifery,Iran, the grounded theory (GT) method proposed by Strauss and Corbin was used. Data were collected through 29 semi-structured interviews, including 17 interviews with faculty members and 12 interviews with nursing students using purposeful and theoretical sampling. Using Strauss and Corbin’s method, the data were compared partially, deeply, and persistently. Results: The main concern of this study was a knowledge deficit in clinic knowledge by nursing students, which seems to indicate a shortage in learning and acquiring knowledge. The core category was the relative acquisition of knowledge of nursing which is not advanced. Within a context of relative dynamism, factors that facilitate or constrain knowledge acquisition were examined within a process of the acquisition of theoretical knowledge and its application to clinical nursing knowledge along with nursing experience. The consequence is expected to bean improvement in nursing knowledge among nursing students in clinical practice Conclusion: Acquiring up-to-date and advanced nursing knowledge is essential in the development process. It is necessary to encourage the acquisition of knowledge, which primarily includes knowledge acquisition in the mission and strategic planning of nursing education.As a result, there should be operational planning for improvements in the gain of practical knowledge.